Surgical Strategy for Contralateral Groin Management in Patients Scheduled for Unilateral Inguinal Hernia Repair: An International Web-Based Surveymonkey® Questionnaire: Strategy for Contralateral Groin Management during Inguinal Hernia Repair. (September 2021) - Johansen, Niels; Miserez, Marc; de Beaux, Andrew; Montgomery, Agneta; Faylona, Jose Macario; Carbonell, Alfredo; Bisgaard, Thue
Background: A contralateral occult inguinal hernia is frequently observed in patients planned for a unilateral laparoscopic inguinal hernia repair. Surgical strategy for contralateral groin management in patients scheduled for an endo-laparoscopic unilateral inguinal hernia repair is controversial and based on questionable evidence. This study aimed to gather international opinion concerning the surgical strategy for the contralateral asymptomatic side when no hernia or lipoma is clinically evident at the preoperative examination or anamnesis. Methods: An international Internet-based questionnaire was sent to all the members of the European Hernia Society, the Americas Hernia Society, and the Asia Pacific Hernia Society. The clinical scenario for responders was a patient with a unilateral symptomatic inguinal hernia planned for endo-laparoscopic repair with no preoperative symptoms/lump on the contralateral side. Results: A total of 640 surgeons replied (response rate = 26%), of whom 506 were included for analysis. Most surgeons had performed > 300 repairs. The preferred surgical technique was evenly distributed between laparoscopic total extraperitoneal repair and laparoscopic transabdominal preperitoneal repair. In total, 54% preferred to implant a prophylactic mesh on the contralateral side when an occult hernia was found, 47% when a lipoma was found, and 6% when no occult hernia/lipoma was identified. Conclusions: Mesh implementation was preferred by half of the endo-laparoscopic hernia surgeons for a contralateral occult hernia and/or lipoma. Although not supported by strong evidence, mesh implantation on the asymptomatic contralateral side might be cost-effective and perhaps beneficial in the long term but could be offset by increased risk of chronic pain and sexual dysfunction.